The Inhibition of Antibiotic Production in Streptomyces coelicolor Over-Expressing the TetR Regulator SCO3201 IS Correlated With Changes in the Lipidome of the Strain - Zhang, Jun; Liang, Qiting; Xu, Zhongheng; Cui, Miao; Zhang, Qizhong; Abreu, Sonia; David, Michelle; Lejeune, Clara; Chaminade, Pierre; Virolle, Marie-Joelle; Xu, Delin (Frontiers in Microbiology, 2020)
In condition of over-expression, SCO3201, a regulator of the TetR family was previously shown to strongly inhibit antibiotic production and morphological differentiation in Streptomyces coelicolor M145. In order to elucidate the molecular processes underlying this interesting, but poorly understood phenomenon, a comparative analysis of the lipidomes and transcriptomes of the strain over-expressing sco3201 and of the control strain containing the empty plasmid, was carried out. This study revealed that the strain over-expressing sco3201 had a higher triacylglycerol content and a lower phospholipids content than the control strain. This was correlated with up- and down- regulation of some genes involved in fatty acids biosynthesis (fab) and degradation (fad) respectively, indicating a direct or indirect control of the expression of these genes by SCO3201. In some instances, indirect control might involve TetR regulators, whose encoding genes present in close vicinity of genes involved in lipid metabolism, were shown to be differentially expressed in the two strains. Direct interaction of purified His6-SCO3201 with the promoter regions of four of such TetR regulators encoding genes (sco0116, sco0430, sco4167 and sco6792) was indeed demonstrated. Furthermore, fasR (sco2386), encoding the activator of the main fatty acid biosynthetic operon, sco2386-sco2390, was also shown to be an illegitimate positive regulatory target of SCO3201. Altogether our data demonstrated that the sco3201 over-expressing strain accumulates TAG and suggested that degradation of fatty acids was reduced in this strain. This would result into a reduced acetyl-CoA availability that would impair antibiotic biosynthesis either directly or indirectly.